Humanitarian law in action within Africa - Moore, Jennifer, 1961- (Oxford University Press, 2012)
In Humanitarian Law in Action within Africa, Jennifer Moore studies the role and application of humanitarian law by focusing on African countries that are emerging from civil wars. Moore offers an overview of international law, including its essential vocabulary, and describes four particular subfields of international law: international humanitarian law, international human rights law, international criminal law, and international refugee law. After setting forth this overview, Moore considers practical mechanisms to implement international humanitarian law, focusing specifically on the exper.